Food advertisements in Malaysia ideal tools for da'wah? - Mokhtar, Aida; Wahid, Norashikin (2022)
The increased usage of advertisements in Malaysia makes their examination important as evident through the potential increase in ADEX in the second quarter of 2022 as reported by Kenanga Research. The notion of advertisements affecting target audiences in ways that could shape their perception of reality makes their examination important. Thus, advertising not only brings together buyers and sellers at the marketplace but also educates us on ideals and makes us better people. When advertisements are used to bring us to the right path, this entails their use as tools for da’wah. Temporal (2011) lists some Islamic values that could be used for the purpose of global branding that could be imbued in advertisements. The question of whether they are found in video advertisements of halal food products in Malaysia and how they have been incorporated will be at the centre of their examination using qualitative content analysis in the proposed study. It is expected that the advertisements produced and shown to a Muslim majority audience would contain Islamic values upholding the expectations of the authorities.